Hepatocellular carcinoma: pathogenesis, molecular mechanisms, and treatment advances - Ding, Zhixian; Wang, Lusheng; Sun, Jiting; Zheng, Lijie; Tang, Yu; Tang, Heng (Frontiers in Oncology, 2025)
Hepatocellular Carcinoma (HCC), a highly prevalent malignancy, poses a significant global health challenge. Its pathogenesis is intricate and multifactorial, involving a complex interplay of environmental and genetic factors. Viral hepatitis, excessive alcohol consumption, and cirrhosis are known to significantly elevate the risk of developing HCC. The underlying biological processes driving HCC are equally complex, encompassing aberrant activation of molecular signaling pathways, dysregulation of hepatocellular differentiation and angiogenesis, and immune dysfunction. This review delves into the multifaceted nature of HCC, exploring its etiology and the intricate molecular signaling pathways involved in its development. We examine the role of immune dysregulation in HCC progression and discuss the potential of emerging therapeutic strategies, including immune-targeted therapy and tumor-associated macrophage interventions. Additionally, we explore the potential of traditional Chinese medicine (TCM) monomers in inhibiting tumor growth. By elucidating the complex interplay of factors contributing to HCC, this review aims to provide a comprehensive understanding of the disease and highlight promising avenues for future research and therapeutic development.